1845-64 Or. Gen. Laws 531, ch. 43, § 527 - (:unkn) unknown (General Publisher, 1864)
If any person shall assault, or assault and beat another with a cowhide, whip, stick or like thing, having at the time in his possession a pistol, dirk or other deadly weapon, with intent to intimidate and prevent such other from resisting or defending himself, such person upon conviction thereof, shall be punished by imprisonment in the penitentiary not less than one, nor more than ten years.
--
Keywords: COMMITTING CRIME W/ WEAPON